AN ACOUSTICAL CONTRASTIVE ANALYSIS OF SUNDANESE CENTRAL VOWELS - Yusup Irawan (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
The first, this research is intended to identify acoustic profiles of the two central vowels in Sundanese, viz /ə/ and /ö/. The second, this research is intended to searches the acoustic contrasts between the two vowels. Experimental method was applied in this research. The result shows that vowel /ə/ has higher first fromant (F1) than vowel /ö/ both at opened syllable and at closed syllable. However, for the other acoustic properties—the second formant (F2), fundamental frequency (Fo), duration (ms), and intensity (dB)—vowel /ö/ has higher acoustic values than vowel /ə/. In correlation with the second research objective, viz to search acoustic properties which contrast the two central vowels, it’s found that all acoustic properties (F1, F2, Fo, duration and intensity) contrast the two Sundanese central vowels. All statistical tests which were applied show the results that there are significant differences of the acoustic properties between both central vowels.